Using the size and position of drumlins to understand how they grow, interact and evolve - Ely, Jeremy C.; Clark, Chris D.; Spagnolo, Matteo; Hughes, Anna L.C.; Stokes, Chris R. (Earth Surface Processes and Landforms, 2018)
Drumlins are subglacial bedforms streamlined in the direction of ice flow. Common in deglaciated landscapes, they have been widely studied providing rich information on their internal geology, size, shape, and spacing. In contrast with bedform investigations elsewhere in geomorphology (aeolian and fluvial dunes and ripples for example) most drumlin studies derive observations from relict, and thus static features. This has made it difficult to gain information and insights about their evolution over time, which likely hampers our understanding of the process(es) of drumlin formation. Here we take a morphological approach, studying drumlin size and spacing metrics. Unlike previous studies which have focussed on databases derived from entire ice sheet beds, we adopt a space-for-time substitution approach using individual drumlin flow-sets distributed in space as proxies for different development times/periods. Framed and assisted by insights from aeolian and fluvial geomorphology, we use our metric data to explore possible scenarios of drumlin growth, evolution and interaction. We study the metrics of the size and spacing of 36 222 drumlins, distributed amongst 71 flow-sets, left behind by the former British-Irish Ice Sheet, and ask whether behaviour common to other bedform phenomena can be derived through statistical analysis. Through characterizing and analysing the shape of the probability distribution functions of size and spacing metrics for each flow-set we argue that drumlins grow, and potentially migrate, as they evolve leading to pattern coarsening. Furthermore, our findings add support to the notion that no upper limit to drumlin size exists, and to the idea that perpetual coarsening could occur if given sufficient time. We propose that the framework of process and patterning commonly applied to non-glacial bedforms is potentially powerful for understanding drumlin formation and for deciphering glacial landscapes.